La disuguaglianza socioeconomica in America Latina e Colombia. Panoramica sulle politiche pubbliche per la redistribuzione della ricchezza (2022)
Abstract In Latin America, the struggle against socioeconomic inequality is a recurring theme of regional and global political debate. In fact, despite the progress made during the 2008-2014 commodity price boom, the various governments have failed to transform reality in a more equitable direction. Through a statistical-documentary review, this paper aims to examine the tax system of some of the main Latin American countries, with a particular focus on the Colombian case. It emerges that, with the exception of Argentina, Brazil and Cuba, the Latin American reality is still very far from the values of tax revenues and social spending of the OECD average. This differential is caused in particular by a substantially regressive approach to taxation, accompanied by high levels of avoidance and evasion. The result is that welfare services (pensions, health, and education) do not receive the necessary resources for their effective, efficient, and universal functioning. This thus discredits their credibility, especially in the eyes of the middle and rich classes who often purchase these services from the private sector. By virtue of this dynamic, Latin American welfare is thus transformed into a kind of charity of the middle-high classes towards the less ones. This ideological outlook is in fact one of the greatest obstacles to a progressive transformation of the Latin American tax system, which is also distinguished by a very low taxation of the income and wealth of individuals compared to other countries of greater industrialization. Keywords: Welfare state, fiscal policy, social inclusion, Latin America, Carlo Tassara.